Pengaruh Struktur Kepemilikan Saham Pada Perusahaan Bumn Terhadap Struktur Modal Dan Kinerja Keuangan - Suhartono (Journal of Economic, Management and Entrepreneurship, 2023)
This study aims to examine the effect of ownership structure as measured by managerial and institutional ownership on capital structure as measured by debt to total assets, debt to total equity and long term debt to total equity and financial performance as measured by return on assets, return on equity and return on investment. This study also uses partial least squares (PLS) analysis for the influence of exogenous and endogenous variables which ultimately affect financial performance. The research sample is a state-owned company (BUMN) listed on the Indonesia Stock Exchange with a research period of 2013 - 2017. Data were obtained from the Data Stream and IDX website. By using the PLS analysis of the fit measurement model, does ownership structure have a positive effect on financial performance, ownership structure has a positive effect on capital structure and capital structure has a positive effect on financial performance.